What are the patient factors that impact on decisions to progress to total knee replacement? A qualitative study involving patients with knee osteoarthritis - Jane Gunn; Darshini Ayton; Michelle M Dowsey; Jo-Anne Manski-Nankervis; Samantha Bunzli; Penny O'Brien (BMJ Open)
Objectives General practitioners (GPs) are often the first health professionals to assess patients with osteoarthritis (OA). Despite clinical guideline recommendations for non-surgical intervention as first-line therapies, the most frequent referral from a GP for a person with knee OA is to an orthopaedic surgeon. The aim of our study was to explore patient factors that impact on the decision to progress to total knee replacement (TKR), including the experience of patients in general practice, their perceptions of their condition, and their access and use of community-based allied health interventions.Design Qualitative investigation using semi-structured interviews. The Candidacy framework was selected as a lens to examine the factors driving healthcare access. Data were analysed using a thematic analysis approach. Codes identified in the data were mapped to the seven Candidacy domains. Themes corresponding to each domain were described.Setting A public hospital in Melbourne, Australia.Participants 27 patients with knee OA who were on a waiting list to undergo TKR.Results Ten themes described factors influencing access and use of non-surgical interventions and decision-making for undergoing TKR: (1) History of knee problems, change in symptoms; (2) Physical and psychosocial functioning (Identification of Candidacy); (3) GP and social networks as information sources, access to care (Navigation); (4) Referral pathways (Permeability of services); (5) Communication of impact (Appearances at health services); (6) GP-Surgeon as the predominant referral pathway (Adjudications); (7) Physical activity as painful; (8) Beliefs about effectiveness of non-surgical interventions (Offers and resistance); (9) Familiarity with local system; and (10) Availability (Operating conditions and local production of Candidacy).Conclusions Using the Candidacy framework to analyse patients’ experiences when deciding to progress to TKR highlighted missed opportunities in general practice to orient patients to first try non-surgical interventions. Patients with knee OA also require improved support to navigate allied health services.